2010
DOI: 10.1159/000315895
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Evolution in African Cichlid Fish: Contributions from the Physical Mapping of Repeated DNAs

Abstract: Cichlid fishes have been the subject of increasing scientific interest because of their rapid adaptive radiation that has led to extensive ecological diversity and because of their enormous importance to tropical and subtropical aquaculture. To further understanding of chromosome evolution among cichlid species, we have comparatively mapped the SATA satellite DNA, the transposable element ROn-1, and repeated sequences in the bacterial artificial chromosome clone BAC-C4E09 on the chromosomes of a range of Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 57 publications
2
61
1
1
Order By: Relevance
“…Additionally, there are no observed karyotypic differences between species having male or female heterogametic sex-determination mechanisms [Kornfield et al, 1979;Majumdar and McAndrew, 1986;Ferreira et al, 2010].…”
Section: Cytogenetic Researchmentioning
confidence: 97%
“…Additionally, there are no observed karyotypic differences between species having male or female heterogametic sex-determination mechanisms [Kornfield et al, 1979;Majumdar and McAndrew, 1986;Ferreira et al, 2010].…”
Section: Cytogenetic Researchmentioning
confidence: 97%
“…In O. niloticus the largest chromosome pair might have originated by chromosome fusions [Chew et al, 2002;Ferreira et al, 2010] and is recognized as the sex chromosome [Carrasco et al, 1999;Griffin et al, 2002]. It has been broadly reported that TEs have been important to genome evolution in a range of species, causing in some cases loss and gain of sequences and chromosomal rearrangements [Lyttle and Haymer, 1992;Cáceres et al, 1999Cáceres et al, , 2001Zhang and Peterson, 1999;Evgen'ev et al, 2000;Biémont and Vieira, 2006].…”
Section: General Features Of Rex Elements In the Fish Chromosomesmentioning
confidence: 99%
“…As the largest chromosome pair of O . niloticus may reflect an ancient state for the sex chromosome in the tilapiine group [Cnaani et al, 2008], the accumulation of Rex elements along the length of the q arm, together with other repeated sequences [Harvey et al, 2003;Ferreira and Martins, 2008;Ferreira et al, 2010], indicates that the repetitive elements played important roles in the differentiation of sex chromosomes in the group. Similarly, in C. hamatus , the retrotransposon Rex3 has also accumulated in the long arm of the male Y chromosome, indicating that the TE could have been involved in the fusion process and molecular differentiation that created the sex chromosomes in this species [Ozouf-Costaz et al, 2004].…”
Section: General Features Of Rex Elements In the Fish Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…This mismatch may have been caused by chromosome rearrangements during the evolutionary process. The number of chromosomes in cichlid species has changed during evolution [Ferreira et al, 2010;Poletto et al, 2010a], and a high frequency of chromosome rearrangements is suggested by fluorescence in situ hybridization (FISH) analyses [Mazzuchelli et al, 2011[Mazzuchelli et al, , 2012. Furthermore, the LGs may not match in different cichlid species because the existing microsatellite markers isolated from one species may not be present in the species of interest.…”
mentioning
confidence: 99%